(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2020)
The article 67 part e) of the Criminal Code establishes the guilty verdict as act that interrupts the limitation of criminal liability, even if the decision is not final. Although the norm seems to be easily to interpret, within case-law it is possible to see that judges interpret it in different ways: while some of them delimit the norm to the first sentence, others increase the meaning to the revisions of the judgment. In this paper, I will analyze the arguments used within case-law and I will make a critical study about how must be the norm interpreted. Taking into account the basis and the principles of the criminal process and the constitutional guaranties I am going to defend the idea that, the fairest interpretation must be restrictive. My study, since it is ultimately an issue of hermeneutic, will be made not only from criminal procedural law and constitutional law, but also from philosophy of law.